Computer-Based National Assessment Policy (ANBK) at SD IT Qordova Bandung as An Alternative to The National Examination - Junaedi, Dedi; Sa’diah, Titin; Zumailah, Elly; Qomaruzzaman, Bambang; Yuliati Zaqiah, Qiqi (Pusat Penerbitan Universitas (P2U) Unisba, 2024)
The government issued a maximum competency assessment policy, abbreviated to (AKM), as a replacement for the National Examination which was deemed to have failed in improving the quality of education. AKM is a fundamental assessment for students in the development of abilities which is an evaluation of the extent to which education has been successful. So the government provides policies so that they can be implemented in educational institutions to encourage teachers and school principals to improve the quality of learning and evaluation. Maximum National Assessment (AKM) Next known as Computer-Based National Assessment (ANBK) which is carried out at the middle school level, namely in class 5 for SD/MI, class 8 for SMP/MTS, and class 11 for SMA/MA/SMK. This policy is not easy to realize, in fact it has become a tangled thread in the world of education, so the aim of this research is to analyze the AKM policy rolled out by the Ministry of Culture and Education in socializing it, especially at SDIT Qordova Rancaekek Bandung. The method used is a qualitative method with a descriptive approach through analysis by studying manuscripts and documentationliberia riserct through data analysis. A summary of the research results shows that the government has succeeded in implementing the maximum competency assessment (AKM), known as ANBK, to all educational institutions throughout Indonesia. Even though there are still many shortcomings in applying it to educational institutions, this policy has been implemented. The conclusion of the national assessment is a new breakthrough in policy to improve the quality of education through maximum competency assessment (AKM). SD IT Qordova has implemented ANBK well and smoothly even though there are still many shortcomings and needs improvement, one of which is a lack of resources and laboratory space as a place to carry out ANBK.